Isolation and Characterization of Bioactive Anti-inflammatory Flavonoids from Arisaema tortuosum Tubers - Chakraborty, Priyanka; Mazumder, Kamalika; Nath Bala, Nripendra; Das, Sudipta (Asian Journal of Chemistry, 2020)
Present study was focused on the isolation and characterization of the anti-inflammatory compound(s) from the methanolic extracts of Arisaema tortuosum tuber by column chromatography, TLC, FT-IR, 1H, 13C NMR and HR-MS. Among all the fractions obtained A. tortuosum fraction 3 (PC-1) and fraction 5 (PC-2) showed significant in vivo anti-inflammatory activity. This study endorsed that the isolated bioactive compound PC-2 showed better anti-inflammatory activity at a dose of 25 mg/Kg BW. The results indicate that PC-2 and PC-1 methanolic extract of A. tortuosum tuber may be competing for the tent in the therapy of inflammatory ailments.